2015
DOI: 10.1016/j.paid.2015.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Dispositional mindfulness in people with HIV: Associations with psychological and physical health

Abstract: We used a Stress and Coping model to examine the association of dispositional mindfulness, defined as the tendency to intentionally bring nonjudgmental attention and awareness to one’s experience in the present moment, with psychological and physical health in adults with HIV. Data were collected at baseline of a randomized controlled trial of Mindfulness-Based Stress Reduction (MBSR). Four facets of mindfulness (acting with attention/awareness, nonjudging of inner experience, observing, and describing) were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 42 publications
4
8
1
Order By: Relevance
“…For example, early childhood adversity has been associated with greater threat appraisals and affective regulation difficulties, both associated with alterations in stress physiology (Repetti, Taylor, & Seeman, 2002;Woody & Szechtman, 2011). This pattern of appraisal and affective reactivity may be particularly salient in shaping physiological responses to stress and likely plays a prominent role in age-related processes and disease (Epel et al, 2018;Moskowitz et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For example, early childhood adversity has been associated with greater threat appraisals and affective regulation difficulties, both associated with alterations in stress physiology (Repetti, Taylor, & Seeman, 2002;Woody & Szechtman, 2011). This pattern of appraisal and affective reactivity may be particularly salient in shaping physiological responses to stress and likely plays a prominent role in age-related processes and disease (Epel et al, 2018;Moskowitz et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have investigated these issues with great emphasis on the role of mindfulness [16][17][18][19]. In Western populations, it has been shown that a higher level of mindfulness is negatively associated with stress [19] and depression [17]. As for academic performance, mindfulness also has a positive effect on grade point average (GPA) [20].…”
Section: Introductionmentioning
confidence: 99%
“…, Moskowitz et al . , Silver et al . ), or alternatively on coping as a distinct process (Pennebaker et al .…”
Section: Introductionmentioning
confidence: 99%
“…Within the literature coping has been extensively discussed, mainly within the field of health psychology (Folkman et al 1986, Hagger and Orbell 2003, Leventhal et al 1992, Yi-Frazier et al 2015. Much of this research has focused on the categorisation of various 'coping strategies' (Dunkelschetter et al 1992, Dempster et al 2015, Moskowitz et al 2015, Silver et al 2002, or alternatively on coping as a distinct process (Pennebaker et al 1990) that overlaps with the concept of adaptation to illness (Charmaz 1995, Persson et al 2013. Psychological studies on coping are supported by health-related quality of life research that has led to the development of metrics such as the COPE inventory (Carver et al 1989) and the Ways of Coping Questionnaire (Folkman and Lazarus 1988); these and other measures are used to assess aspects of coping (Kato 2015) and their relationships to health outcomes (Penley et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation